2016
DOI: 10.3892/ol.2016.5291
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effect of luteolin on redox homeostasis and inflammatory cytokines in a mouse model of liver cancer

Abstract: Abstract. Liver cancer is one of the leading causes of cancer-associated mortality worldwide. Due to changes in lifestyle and daily exposure to various chemicals, which may lead to chemical intoxication, liver cancer has become a prominent disease in humans. Chemical-induced carcinogenesis in experimental animals has become a reliable model for the investigation of liver cancer-associated biological alterations that may mimic human hepatic cancer. Liver cancer in BALB/c mice was induced by administering diethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 29 publications
6
13
0
Order By: Relevance
“…These data were consistent with as previously reported in cadmium intoxication model in Wistar rats [9]. By comparison, some studies evaluated the extract of a medicinal herb from India called Melastoma Malabathricum Linn (MM) carcinogenesis model and luteolin (LUT) a natural polyphenolic flavone present in various fruits and vegetables using murine model of liver carcinogenesis [56]. It was reported that both MM and LUT extracts act as antioxidant agents by re-establishing the activity of the enzymes as a result of increasing the expression of SOD-Mn.…”
Section: Discussionsupporting
confidence: 90%
“…These data were consistent with as previously reported in cadmium intoxication model in Wistar rats [9]. By comparison, some studies evaluated the extract of a medicinal herb from India called Melastoma Malabathricum Linn (MM) carcinogenesis model and luteolin (LUT) a natural polyphenolic flavone present in various fruits and vegetables using murine model of liver carcinogenesis [56]. It was reported that both MM and LUT extracts act as antioxidant agents by re-establishing the activity of the enzymes as a result of increasing the expression of SOD-Mn.…”
Section: Discussionsupporting
confidence: 90%
“…The antioxidant potential of LUT was previously illustrated by other authors [22,46,57]. Flavonoids, including LUT, exert their antioxidant properties through several mechanisms involving the ability to trap ROS via chain breaking properties, thereby exerting their defensive effects on cellular macromolecules, in addition to increasing the cellular level of total GSH and suppressing the peroxidation of lipids [57,58]. Additionally, LUT employs its antioxidant ability through scavenging both ROS and RNS, chelating transition metals such as iron and copper that may cause oxidative damage through the Fenton reaction, suppression of pro-oxidant enzymes and enhancing activities of antioxidant enzymes [59][60][61].…”
Section: Discussionmentioning
confidence: 63%
“…Pre-treatment with LUT improved the Pb-induced oxidative damage by elevating SOD, CAT, GR, GPx, and GSH and lowering the MDA level in hepatic tissue. The antioxidant potential of LUT was previously illustrated by other authors [22,46,57]. Flavonoids, including LUT, exert their antioxidant properties through several mechanisms involving the ability to trap ROS via chain breaking properties, thereby exerting their defensive effects on cellular macromolecules, in addition to increasing the cellular level of total GSH and suppressing the peroxidation of lipids [57,58].…”
Section: Discussionmentioning
confidence: 85%
“…Studies have shown that flavonoids have anti-tumor and anti-inflammatory properties and are capable of reducing the serum levels of Th1 cytokines [ 22 ]. The presence of major flavonoids such as apigenin, quercetin, and luteolin in ajwa could be one of the reason for reduced serum levels of proinflammatory cytokines (IL-1β, TNF-α and IL-6), and hepatoprotection observed in DEN-induced HCC in rats [ 23 , 24 ]. Furthermore, lower levels of GM-CSF by itself effectively reduces the concentrations of other proinflammatory cytokines IL-1β and TNF-α [ 25 ].…”
Section: Discussionmentioning
confidence: 99%